2023
DOI: 10.1002/anie.202300162
|View full text |Cite
|
Sign up to set email alerts
|

Type I Photosensitizer Targeting G‐Quadruplex RNA Elicits Augmented Immunity for Cancer Ablation

Abstract: Type I photodynamic therapy (PDT) represents a promising treatment modality for tumors with intrinsic hypoxia. However, type I photosensitizers (PSs), especially ones with near infrared (NIR) absorption, are limited and their efficacy needs improvement via new targeting tactics. We develop a NIR type I PS by engineering acridinium derived donor-π-acceptor systems. The PS exhibits an exclusive type I PDT mechanism due to effective intersystem crossing and disfavored energy transfer to O 2 , and shows selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…[9] G4-targeting BAMAmediated photodynamic therapy can elicit augmented immunity for cancer ablation. [10] The development of strategies to enhance cancer immunotherapy by stimulating immune responses has progressed rapidly in recent years. As promising therapeutic targets, G4s exist widely in regions with vital functions, [11] but the role of G4s in immunotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] G4-targeting BAMAmediated photodynamic therapy can elicit augmented immunity for cancer ablation. [10] The development of strategies to enhance cancer immunotherapy by stimulating immune responses has progressed rapidly in recent years. As promising therapeutic targets, G4s exist widely in regions with vital functions, [11] but the role of G4s in immunotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the G4 binders, pyridostatin and PhenDC3, have been found to stimulate the cGAS‐STING pathway at low doses [9] . G4‐targeting BAMA‐mediated photodynamic therapy can elicit augmented immunity for cancer ablation [10] . The development of strategies to enhance cancer immunotherapy by stimulating immune responses has progressed rapidly in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) that employs photosensitizers to yield reactive oxygen species (ROS) for tumor eradication has been considered as a potentially effective therapeutic strategy for tumors with benefits of noninvasiveness, spatiotemporal controllability, and negligible drug resistance. Traditional PDT is based on type II photochemical processes in which the energy of excited photosensitizers is directly transferred to O 2 to form singlet oxygen ( 1 O 2 ), which is of strong O 2 -dependence. However, the anticancer efficacy of PDT is severely weakened by the inherent hypoxic microenvironment of solid tumors. , To overcome this dilemma, a potential tactic is to develop type I photosensitizers that utilize electron/proton transfer to produce reactive species such as superoxide anions (O 2 •– ) and hydroxyl radicals (OH·). The formed O 2 •– can subsequently initiate a series of biological cascade reactions, resulting in the recycling of O 2 accompanied by the generation of highly cytotoxic OH·. , Therefore, PDT based on type I photochemical processes shows low dependence on O 2 and thus is a more reliable approach toward the treatment of hypoxic tumors in the clinic compared to type II PDT.…”
mentioning
confidence: 99%
“…Carbon dots (CDs) are carbon nanoparticles that have emerged as promising photosensitizer agents due to their numerous merits including easy preparation, excellent biocompatibility, good water dispersibility, and rich photophysical properties. Moreover, the surface state of CDs could be readily tuned by elaborate choice of the starting materials or postmodification, endowing their targeting capability to specific organelles or components. Among them, ribonucleic acid (RNA), which plays active roles in the coding, regulation, and expression of genes, represents an efficient and ideal target site in various therapeutic modalities on account of its poor tolerance to ROS. To date, there are a few reports on the synthesis of RNA or nucleolus-targeted CDs. For example, Lin and Wu et al demonstrated the potential of CDs in drug delivery by advantage of their effective accumulation in nucleolus. Very recently, our group reported the rational design of RNA-targeting CDs for dynamic imaging of stress granules based on levofloxacin as it is an antibiotic that works by relying on the high binding affinity between levofloxacin and nucleic acids . However, the individual CDs hardly produce ROS, and thus, additional conjugation of drug or photosensitizer is required for treatment.…”
mentioning
confidence: 99%